Information structuring improves recall of emergency discharge information: a randomized clinical trial. Issue 6 (3rd July 2017) - Ackermann, Selina; Ghanim, Leyla; Heierle, Anette; Hertwig, Ralph; Langewitz, Wolf; Mata, Rui; Bingisser, Roland
Abstract: This article examines the extent to which structuring Emergency Department discharge information improves the ability to recall that information, and whether such benefits interact with relevant prior knowledge. Using three samples of students with different levels of prior medical knowledge, we investigated the amount of information recalled after structured vs. non-structured presentation of information. Across all student samples, the structured discharge information led to a relative increase in recalled items of 17% compared to non-structured discharge information ( M = 9.70, SD = 4.96 vs. M = 8.31, SD = 4.93). In the sample with least medical knowledge, however, the structured discharge information resulted in a relative increase in recall by 42% ( M = 8.12 vs. M = 5.71). These results suggest that structuring discharge information can be a useful tool to improve recall of information and is likely to be most beneficial for patient populations with lower levels of medical knowledge.